A method of predicting noise equivalent level value in urban structure - MAKAREWICZ, Rufin; KERBER, Gabriela (Archives of Acoustics, 1978)
The paper presents a method of predicting the noise equivalent level value in urban structure. Unlike the methods used thus far, the presented method consists in determination of a parameter a which is a measure of the energy reaching the observation point during motion of a single source. The method is very laborious and, therefore, the paper presents a solution of the problem of determination of the minimum number of the measurements of the parameter a, necessary to determine the noise equivalent level value with a preset accuracy.